2019
DOI: 10.3389/fgene.2019.00758
|View full text |Cite
|
Sign up to set email alerts
|

Predicting lncRNA-miRNA Interaction via Graph Convolution Auto-Encoder

Abstract: The interaction of miRNA and lncRNA is known to be important for gene regulations. However, the number of known lncRNA-miRNA interactions is still very limited and there are limited computational tools available for predicting new ones. Considering that lncRNAs and miRNAs share internal patterns in the partnership between each other, the underlying lncRNA-miRNA interactions could be predicted by utilizing the known ones, which could be considered as a semi-supervised learning problem. It is shown that the attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…This model analyzes the patterns in large-scale expression profiles of known lncRNA–miRNA interactions and it is based on the assumption that lncRNAs that are very similar to each other tend to have similar interaction or non-interaction patterns with miRNAs and vice versa [ 182 ]; (ii) the Graph Convolution for novel LncRNA-MiRNA Interactions (GCLMI), based on graph convolutional networks (GCNs), a powerful type of neural network designed to work directly on graphs and leverage their structural information. GCLMI is a network-based algorithm that considers known lncRNA–miRNA interactions along with lncRNA and miRNA expression levels, and aims to calculate the possibility that an lncRNA–miRNA pair is interactive in biological processes [ 183 ]; (iii) the Linear Neighbour Representation to predict LncRNA-MiRNA Interactions (LNRLMI) is based on the implementation of an lncRNA–miRNA network realized combining the known interaction network and similarities based on expression profiles of lncRNAs and miRNAs. To predict the new links of the known lncRNA–miRNA interaction network, a linear optimization, a semi-supervised model, has been added to this model [ 184 ].…”
Section: Prediction Of Lncrna–mirna Interactionsmentioning
confidence: 99%
“…This model analyzes the patterns in large-scale expression profiles of known lncRNA–miRNA interactions and it is based on the assumption that lncRNAs that are very similar to each other tend to have similar interaction or non-interaction patterns with miRNAs and vice versa [ 182 ]; (ii) the Graph Convolution for novel LncRNA-MiRNA Interactions (GCLMI), based on graph convolutional networks (GCNs), a powerful type of neural network designed to work directly on graphs and leverage their structural information. GCLMI is a network-based algorithm that considers known lncRNA–miRNA interactions along with lncRNA and miRNA expression levels, and aims to calculate the possibility that an lncRNA–miRNA pair is interactive in biological processes [ 183 ]; (iii) the Linear Neighbour Representation to predict LncRNA-MiRNA Interactions (LNRLMI) is based on the implementation of an lncRNA–miRNA network realized combining the known interaction network and similarities based on expression profiles of lncRNAs and miRNAs. To predict the new links of the known lncRNA–miRNA interaction network, a linear optimization, a semi-supervised model, has been added to this model [ 184 ].…”
Section: Prediction Of Lncrna–mirna Interactionsmentioning
confidence: 99%
“…Huang et al proposed the first large-scale lncRNA–miRNA predictive model using a network diffusion method on sequence information, expression profiles, and biological function ([ 93 , 94 ]). Similarly, Huang et al proposed GCN-based model, graph convolution for novel lncRNA–miRNA interactions (GCLMI), to predict lncRNA–miRNA interactions [ 63 ]. Based on the proposed model, which combines graph convolution and an auto-encoder, Huang et al found that the area under the curve (AUC) for the predictor was around 0.85, indicating that DL-based methods are important contributors in this research field.…”
Section: Summary Of the Lncrnaome Research Domains Where Deep Learmentioning
confidence: 99%
“…proposed GCN-based model, graph convolution for novel lncRNA-miRNA interactions (GCLMI), to predict lncRNA-miRNA interactions [63]. Based on the proposed model, which combines graph convolution and an auto-encoder, Huang et al found that the area under the curve (AUC) for the predictor was around 0.85, indicating that DL-based methods are important contributors in this research field.…”
Section: Predicting Lncrna-mirna Interactionsmentioning
confidence: 99%
“…miRNAs and lncRNAs interact with each other, organizing an extensive regulatory network that can modulate the expression of genes in transcriptional, posttranscriptional, and posttranslational levels. These two ncRNA families can affect almost all cell cycle aspects, cell division, differentiation, and apoptosis 30 …”
Section: Introductionmentioning
confidence: 99%